2019
DOI: 10.1039/c8nj04602f
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexes of arylselenolate-based ligands: synthesis and catalytic activity in azide–alkyne cycloaddition reactions

Abstract: Arylselenolate-based copper complexes have been synthesized and used as pre-catalysts for azide-alkyne cycloaddition reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Additional references cited within the Supporting Information. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] All experimental procedures and data are described in the Supporting Information.…”
Section: Synthesis Of Cu-tazo-tapbmentioning
confidence: 99%
“…Additional references cited within the Supporting Information. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] All experimental procedures and data are described in the Supporting Information.…”
Section: Synthesis Of Cu-tazo-tapbmentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl 3 ): δ 8.15 (s, 1H), 7.92-7.90 (m, 2H), 7.67-7.66 (m, 2H), 7.47-7.44 (m, 2H), 7.38-7.31 (m, 3H), 2.43 (s, 3H) ppm. 13 C{ 1 H} NMR (125 MHz, CDCl 3 ): δ 148.4, 139.0, 134.9, 130.5, 130.3, 129.0, 128.4, 125.9, 120.5, 117.7, 21.2 ppm. [26] 0.203 g (2 a), 0.…”
Section: General Procedures For the Azide-alkyne Click Reactionmentioning
confidence: 99%
“…[11c] Our group reported a series of copper(II) complexes supported by arylselenolate-based ligands for azide-alkyne cycloaddition in water. [13] Thus, following our continuous interest in the development of well-defined transition metal based catalysts, herein, we report the synthesis, characterization, and catalytic activity of copper(II)-bis(imino)pyridine complexes, 2 a&2 b(Figure 1). The copper(II)-bis(imino)pyridine complexes efficiently catalyze azide-alkyne Click reactions for thesynthesis of 1,4disubstituted 1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, our group has reported the Cu II ‐catalyzed azide‐alkyne cycloaddition reaction in water [9] . As part of our research interest in our group for the development of transition metal based catalysts in heterocyclic synthesis, [10] we became interested to utilize the zinc(II)‐ bis (imino)pyridine complexes as catalysts in azide‐alkyne cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In 2019, our group has reported the Cu II -catalyzed azidealkyne cycloaddition reaction in water. [9] As part of our research interest in our group for the development of transition metal based catalysts in heterocyclic synthesis, [10] we became interested to utilize the zinc(II)-bis(imino)pyridine complexes as catalysts in azide-alkyne cycloaddition reactions. Azide-alkyne cycloaddition reaction catalyzed by zinc metal as catalyst was first reported by Chen et al [11] Greaney et al and Postnikov et al have also reported the zinc mediated azide-alkyne cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%